“Mindeaaret som ingen anden dansk Forsker fik”: Arven efter H.C. Ørsted og elektromagnetismen i 1920 - Marcus Lee Naldal (Slagmark - Tidsskrift for idéhistorie, 2020)
This article shows how the legacy of Hans Christian Ørsted (1777-1851), and his discovery of electromagnetism in 1820, was reconfigured and used by the H.C. english abstracts Ørsted Committee from 1914 before and during the centenary of 1920. Combining Somsen’s (2008) concept of olympic internationalism with uses of the past, I suggest understanding the 1920-centenary as an instance of olympic commemoration [olympisk historiebrug]. I argue that central actors from the committee, e.g. Martin Knudsen (1871-1949) and Kirstine Meyer, née Bjerrum (1861-1941), used Ørsted's nationality to substantiate Denmark’s cultural and scientific achievements. By comparison to pre-twentieth century biographies, I show how the committee re-described Ørsted, i.e. from a scientist [Naturforsker] to being a Danish scientist [dansk Naturforsker]. The committee was deeply concerned with proving the big contributions by the small nation of Denmark, and I show how this relates to cultural politics of the early twentieth century Denmark.